Measurement and analysis of fish pond water temperature field in summer based on fiber Grating string - Guoli Li; Fei Feng; Caihua Qian; Bo Wei (PLoS ONE, 2025)
To solve the problems of low detection efficiency and inability to adapt to distributed measurement in traditional detection methods, a water temperature field detection system based on a fiber Bragg grating string was designed. In this system, six fiber Bragg gratings with different center wavelengths are connected in series on a single fiber optic cable based on wavelength division multiplexing technology. The fiber Bragg grating string is encapsulated in stainless steel tube and vertically fixed in the measured water body of the fish pond. The space division multiplexing technology is employed to collect information from multiple fiber Bragg grating strings. Water temperature measurement experiments were conducted in the summer pond environment. The experimental results show that the daily variation curve of temperature in each water layer of the fish pond is relatively smooth and approximates a cosine function with a 24-hour period. In summer, the daily average water temperature in the pond is no more than 1°C higher than the average air temperature. The difference between the maximum and the minimum water temperature is approximately 2°C. During the daytime, the temperature gradually decreases from the surface to the deeper water layers, whereas at night, the temperature variation among the water layers is minimal. As depth increases, the amplitude of the water temperature curve oscillations gradually decreases, exhibiting exponential decay. However, the peak time gradually lags behind. There is a correlation between the temperatures of the water layers in the fish pond, and the smaller the distance between the water layers, the stronger the correlation. The experimental results obtained in this study are highly significant for real-time services in aquatic planting and aquaculture. Additionally, this measurement method can provide valuable reference and guidance for measuring temperature fields in other fluids.